Effect of vortices on power output of vertical axis wind turbine (VAWT). (February 2020) - Naseem, Ammar; Uddin, Emad; Ali, Zaib; Aslam, Jawad; Shah, Samiur Rehman; Sajid, Muhammad; Zaidi, Ali Abbas; Javed, Adeel; Younis, Muhammad Yamin
Abstract: Performance of a vertical axis wind turbines (VAWTs) is a major focus of research these days. The present research focuses on numerical investigate the performance of a VAWT in the presence of upstream bluff bodies and investigate the impact of vortices shed on the VAWT performance. Designing of wind turbine is performed using Multiple Stream Tube Model which uses turbine power, number of turbine blades, aspect ratio and wind speed as parameter. Simulations are done using Reynolds averaged Navier-Stokes equation. Furthermore, VAWT equipped with three NACA 0018 airfoils is used. In this study, single and two upstream bluff bodies are used and the distance of the VAWT relative to a bluff body is changed to 1D, 2D and 3D (where D is the length and width of bluff body) both along and perpendicular to flow direction in order to find an optimal location for maximum power. This study shows that the deflected wind from the bluff body possess high wind velocity which is 12% higher for single bluff body and 25% higher for two bluff bodies than the free stream wind velocity. Moreover the VAWTs can be deployed downstream of tall urban structures for enhancement of wind turbine power generation.